LEADERSHIP STYLES AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN SMALL AND MEDIUM SCALE FIRMS - Naveed R. Khan; Arsalan Mujahid Ghouri; Marinah Awang (Researchers World - International Refereed Social Sciences Journal, 2021)
The study is conducted to examine the relationship between leadership styles and citizenship behaviour in small and medium scale IT firms operating in Pakistan. The three popular styles of leadership which includes transactional leadership, transformational leadership and charismatic leadership have been studied along with organizational citizenship in 174 IT sector SMEs. This study has explored the correlation between leadership styles that proactively contributes to increase the organizational citizenship at all phases of employee’s behaviour. Statistical findings suggested that different leadership style have been followed at moderate level in small and medium scale IT firms of Pakistan and have strong relationship with organizational citizenship. Moreover, organizational citizenship is proactively contrasted with different leadership styles. This study also validate the assumption that due to the internationalization phenomena IT sector SMEs have been adopted and implemented the management functions in a more comprehensive manner then other service sector SMEs in Pakistan.